FEATURES OF FUTURE TEACHER PROFESSIONAL TRAINING FOR EDUCATIONAL AND NURTURE ACTION - Лідія Хомич (Вісник Кафедри ЮНЕСКО «Неперервна професійна освіта ХХІ століття», 2020)
The basic concepts of the research «action», «interaction» and «activity» were analyzed. It was determined that in today`s conditions preparation for pedagogical activity is considered as a dialectical unity of all its structural components, properties, connections and relations. It was found that the main components of readiness for pedagogical activity are unity of personal and procedural components. The approaches that need to be implemented in the training of future teachers for educational and nurture action were substantiated, in particular: professional selection and propaedeutic preparation of the future teacher, which involves the use of psychological and pedagogical technologies for selecting students for the teaching profession and creating conditions for the professional self-determination of youth, as well as determining its relevance to the requirements of pedagogical activity; improvement of the content of theoretical and practical training in pedagogical universities, therefore it is necessary to revise the content of disciplines for professional training of pedagogical staff at value, content and technological levels; organization of the educational process in a modern pedagogical university should be aimed at the use of effective forms of person-oriented interaction; priority should be given to the role of practical activity in future teacher training for educational and nurture action that provides mastery of the basics of professional skills. It was generalized that development of teachers’ professional competence should include the formation of motivation, initiative, responsibility, active life and professional position.